How to survive college: a guide for new undergraduate students in mental health, study strategies, and time management - Rodgers, Emily, author (Colorado State University. Libraries, 2024)
The rapid changes that occur in the move from high school to undergraduate schooling can be extremely stressful and upsetting to incoming first year students. Some of the key areas of this increased stress come down to three categories; time management, study strategies, and mental health concerns. These three categories work together, so that, if students should be unsuccessful in one area they are at increased risk of being unsuccessful in either two. Largely found massive areas of improvement for first year students in boosting self-regulation and intrinsic motivation to boost time management. In terms of study strategies, spacing and elaborative rehearsal have shown to be the best ways to retain information. While research on mental health in undergraduates has shown to be becoming an increasingly pressing problem, with many universities ill prepared for the mental health crisis. In a survey given out to third and fourth year undergraduates it showcases many students are not fully aware of the empirical supported practices and as such, showcases the need for a better way to spread information.
University Honors Department.
Keywords: mental health; undergraduate students